Rationality, Animality, and Human Nature: Reconsidering Kant’s View of the Human/Animal Relation (Konturen, 2014)
Kant is often criticized for his strict separation of humans and animals as categorically distinct entities. This separation hinges on the fact that, for Kant, humans are rational, while non-human animals are wholly irrational. This essay argues that a strict separation of rational humanity and irrational animality, prominent in many areas of Kant’s thinking, does not characterize his view of the human/animal relation overall. For, within Kant’s theory of human nature, rationality and animality are in fact entwined, with both contributing to the goodness and full realization of human life. Through engagement with a range of Kant’s writings on human nature, it is suggested that Kant’s view of the human/animal relation merits reconsideration by Kant scholars and animal-oriented philosophers alike.